ACUTE TOXICITY STUDY OF THE LEAVES ETHANOLIC EXTRACT OF PICRIA FEL-TERRAE LOUR. - Patilaya, Popi; Irfan Husori, Dadang; Bagus Sumantri, Imam; Sihombing, Simon (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Picria fel-terrae belongs to family Linderniaceae is also known as Pugun tano by Indonesian people. The ethanolic extract of plant leaves has several potential pharmacological activities including antidiabetic, anthelmintic, and antioxidant. However, the toxicity of the plant extract is rarely explored. This work was to investigate toxicity of the leaf ethanolic extract of P. fel-terrae on Artemia salina and male mice. Methods: Acute toxicity of the plant extract was studied by in vitro and in vivo methods. In vitro study was carried out by exposing nauplii to the plant extract at concentrations of 10, 100, 200, 500, and 1000 Î¼g/ml for 48 h. In vivo study was performed on male mice that divided into four groups. Groups I, II, III, and IV were treated with sodium carboxymethyl cellulose 0.5%, the ethanolic extract of plant leaves at doses of 1000, 2000, and 5000 mg/kg bw, respectively. The animal toxic symptoms were observed every day for 14 days. On day 15, the blood of mice was collected to measure alanine aminotransferase, aspartate aminotransferase, and creatinine levels. The effects of plant extract on vital animal organs such as heart, liver, and kidney were also studied. Statistical analysis of data was performed using analysis of variance and followed by Tukey post hoc. Results: The results showed that the leaf ethanolic extract of P. fel-terrae to have weakly toxicity on A. salina with the LC50 of 768.07 Î¼g/ml. At in vivo studies, the toxic symptoms of mice were not identified during experiment with all doses of the plant extract for 14 days. In addition, aspartate aminotransferase and creatinine levels were no significantly different between control and all treatment groups (p>0.05). However, alanine aminotransferase level changed when mice were exposed by the plant extract at the doses of 2.000 and 5.000 mg/kg bw. Although the mice were not dead during experiment, the animal organs such as heart, liver, and kidney were histologically changed. Conclusion: This study suggests that the ethanolic extract of P. fel-terrae leaves has weakly toxicity on A. salina and causes histological changes on male mice organs at the high doses.